Genome-Wide Identification of Seven Polyamine Oxidase Genes in Camellia sinensis (L.) and Their Expression Patterns Under Various Abiotic Stresses - Li, Mengshuang; Lu, Jing; Tao, Mingmin; Li, Mengru; Yang, Hua; Xia, En-hua; Chen, Qi; Wan, Xiaochun (Frontiers in Plant Science, 2020)
Polyamines (PAs) in plant play a critical role in growth and development and in response to environmental stress. Polyamine oxidase (PAO) is a flavin adenine dinucleotide dependent enzyme that plays a major role in PA catabolism. For the first time, PAO genes in tea plant were screened for the whole genome-wide and seven CsPAO genes were identified, which were named CsPAO1-7. Phylogenetic tree analysis revealed seven CsPAO protein sequences classed into three groups, including clade I, III, and IV. Compared with other plants, the tea plant lacked cladeII members.Genetic structure and tissue specific expression analysis showed that there were significant differences among members of the CsPAO gene family. CsPAO4 and CsPAO5 contained more introns and were higher contents in most organs than other members. Heat map showed high response of CsPAO5 to drought stress, while CsPAO1 and CsPAO2 were sensitive to changes in nitrogen nutrition. Furthermore, exogenous abscisic acid (ABA) treatment showed that the expression of most CsPAO genes were significantly induced in the roots and leaves of tea seedings, the content of polyamines most increased except for the decrease of spermidine (Spd) content in the roots, suggesting that ABA has a greater effect on PAs biosynthesis. Anaerobic treatment of picked tea leaves showed that the decomposition of PA s were promoted to a certain extent. The above data help to clarify the role of CsPAO in response abiotic and nitrogen nutritional stresses in tea plants, and provide a reference perspective for the potential influence of PA s on the tea processing quality.